2021
DOI: 10.4240/wjgs.v13.i12.1721
|View full text |Cite
|
Sign up to set email alerts
|

Right sided diverticulitis in western countries: A review

Abstract: BACKGROUND Although the treatment guidelines for left sided diverticulitis are clear, the management of right colonic diverticulitis is not well established. This disease can no longer be ignored due to significant spread throughout Asia. AIM To analyse epidemiology, diagnosis and treatment of right-sided diverticulitis in western countries. METHODS MEDLINE and PubMed searches were performed using the key words “right-sided diverticulitis’’, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
4
0
1
Order By: Relevance
“…9,10 According to various Asian and western studies, RSD mainly affects young adults with an age range between 30 and 45 years. [11][12][13] It could be difficult to distinguish RSD from acute appendicitis since they have similar clinical presentations. However, few studies have reported some differences in order to avoid unnecessary surgery for RSD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 According to various Asian and western studies, RSD mainly affects young adults with an age range between 30 and 45 years. [11][12][13] It could be difficult to distinguish RSD from acute appendicitis since they have similar clinical presentations. However, few studies have reported some differences in order to avoid unnecessary surgery for RSD patients.…”
Section: Discussionmentioning
confidence: 99%
“…These facts have been proclaimed in both Asian and Western series. 3,[35][36][37] Epifani et al 11 published a recent review describing RSD in western countries: only 16 patients out of 422 studied (3.8%) had a recurrence after a nonsurgical treatment with an average follow-up of 32.5 months. Even some of the authors did not report any recurrences in their studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Right-sided diverticulitis is more common in oriental populations, where it typically occurs in younger patients and is often misdiagnosed initially as appendicitis. [ 10 ] Ultrasound findings are similar to left-sided diverticulitis with an outpouching of the bowel containing echogenic material, diverticular wall thickening, and surrounding echogenic fat at the point of maximal tenderness[ 11 ] [ Figure 3 and Video 2 ].…”
Section: R Ight -S Ided D ...mentioning
confidence: 96%
“…Аппендицит и дивертикулит трудно отличить от ВЗОМТ в случае вовлечения придатков и образования абсцесса. Дивертикулез имеет высокую распространенность в общей популяции, а наличие дивертикулов в пораженных сегментах свидетельствует о дивертикулите [72].…”
Section: воспалительные заболевания органов малого таза и тазовые инф...unclassified